2007
DOI: 10.1027/1618-3169.54.1.62
|View full text |Cite
|
Sign up to set email alerts
|

False Memory in a Short-Term Memory Task

Abstract: The Deese/Roediger-McDermott (DRM; Roediger & McDermott, 1995) paradigm reliably elicits false memories for critical nonpresented words in recognition tasks. The present studies used a Sternberg (1966) task with DRM lists to determine whether false memories occur in short-term memory tasks and to assess the contribution of latency data in the measurement of false memories. Subjects studied three, five, or seven items from DRM lists and responded to a single probe (studied or nonstudied). In both experiments, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
56
1
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 18 publications
11
56
1
11
Order By: Relevance
“…This paradigm has been used less often but avoids strategic use of overlapping information. Consistent with the findings for within-list similarity, probe paradigms similarly induce high rates of false recognition for probes with orthographic, phonological, or semantic similarity to a lure (Breadmore, 2007;Coane, McBride, Raulerson, & Jordan, 2007;Crosson et al, 1999;Shulman, 1970). High rates of false recognition are observed for target probes with morphological overlap; indeed the effect may be greater than that attributed to the combination of orthographic/phonological and semantic properties (Breadmore, 2007).…”
supporting
confidence: 68%
“…This paradigm has been used less often but avoids strategic use of overlapping information. Consistent with the findings for within-list similarity, probe paradigms similarly induce high rates of false recognition for probes with orthographic, phonological, or semantic similarity to a lure (Breadmore, 2007;Coane, McBride, Raulerson, & Jordan, 2007;Crosson et al, 1999;Shulman, 1970). High rates of false recognition are observed for target probes with morphological overlap; indeed the effect may be greater than that attributed to the combination of orthographic/phonological and semantic properties (Breadmore, 2007).…”
supporting
confidence: 68%
“…Recent research from our lab has further demonstrated the recalcitrance of the false memory illusion by documenting its occurrence within several seconds of studying brief four-item lists (Atkins & Reuter-Lorenz, 2008;Flegal, Atkins, & Reuter-Lorenz, 2010; see also Coane, McBride, Raulerson, & Jordan, 2007). Flegal et al (2010) used a new experimental paradigm to directly compare false memories in the same participants under short-term memory (STM) and long-term memory (LTM) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Coane, McBride, Raulerson and Jordan (2007) have embedded the DRM lists within a STM recognition (Sternberg) task. With memory set sizes of three, five and seven they measured both accuracy and RT for recognition of list items, the non-presented critical lure and other non-related, non-presented items.…”
mentioning
confidence: 99%